Advancements and future directions of iron oxide nanoparticles in cancer therapy - el-Mallul, Ahmed; Tomasiuk, Ryszard; Jaworski, Piotr; Mughali, Sadia (Contemporary Oncology/Współczesna Onkologia, 2025)
Cancer is one of the leading causes of death worldwide, accounting for approximately 9.6 million deaths annually – 1 in 6 deaths globally. Recent advancements in nanoscience have highlighted the potential of nanomaterials in healthcare applications. Among these, iron oxide nanoparticles (IONPs) stand out due to their magnetic properties, semiconductor behavior, biocompatibility, biodegradability, and low toxicity. These characteristics make them highly valuable in multifunctional biomedical applications, including: magnetic hyperthermia for cancer therapy; targeted drug delivery to minimize chemotherapy side effects; cell labeling and tracking; and bioimaging techniques. This mini-review focuses on the latest developments in IONPs for cancer therapy, evaluating recent research on size, synthesis methods, and biomedical/electrochemical applications of coated, drug-loaded, and targeted nanoparticles. By compiling and comparing key findings, this paper serves as a comprehensive reference for researchers and scientists working on the multidisciplinary applications of nanomaterials.